It's perfectly normal ebook Changing bodies, growing up, sex, gender, and sexual health. - Harris, Robie H. (The Family Library., 2021)
Fully and fearlessly updated, this vital new edition of the acclaimed book on sex, sexuality, bodies, and puberty deserves a spot in every family's library. With more than 1.5 million copies in print, It's Perfectly Normal has been a trusted resource on sexuality for more than twenty-five years. Rigorously vetted by experts, this is the most ambitiously updated edition yet, featuring to-the-minute information and language accompanied by new and refreshed art. Updates include : * A shift to gender-neutral vocabulary throughout * An expansion on LGBTQIA topics, gender identity, sex, and sexuality—making this a sexual health book for all readers * Coverage of recent advances in methods of sexual safety and contraception with corresponding illustrations * A revised section on abortion, including developments in the shifting politics and legislation as well as an accurate, honest overview * A sensitive and detailed expansion on the topics of sexual abuse, the importance of consent, and destigmatizing HIV/AIDS * A modern understanding of social media and the internet that tackles rapidly changing technology to highlight its benefits and pitfalls and ways to stay safe online Inclusive and accessible, this newest edition of It's Perfectly Normal provides young people with the knowledge and vocabulary they need to understand their bodies, relationships, and identities in order to make responsible decisions and stay healthy.